2018
DOI: 10.3168/jds.2018-15319
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of gradual and later weaning ages when feeding high milk replacer rates on growth, textured starter digestibility, and behavior in Holstein calves from 0 to 4 months of age

Abstract: The objectives of this study were to evaluate calf performance, diet digestibility, and behaviors when feeding 4 milk replacer (MR) programs with different MR rates, weaning ages, and MR reduction steps. Male Holstein calves (n = 96; 40 ± 1 kg of body weight; 1 to 2 d of age) were housed in individual pens for 56 d. Feeding programs for MR were 0.66 kg for 35 d; then 0.33 kg for 7 d fed only in the a.m. (0.6 kg); 0.66 kg for 7 d, 0.82 kg for 35 d, 0.33 kg for 4 d in a.m. only, and 0.22 kg for 3 d in a.m. only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
5
15
1
Order By: Relevance
“…Therefore, weaning at 17 wk of age may not trigger abnormal behaviour. The results of the aforementioned and the current study were similar, although we observed behavior only in a small time frame during the d because chewing was found to have no circadian rhythm in calves (11).…”
Section: Rumen Maturation At Early Agesupporting
confidence: 85%
“…Therefore, weaning at 17 wk of age may not trigger abnormal behaviour. The results of the aforementioned and the current study were similar, although we observed behavior only in a small time frame during the d because chewing was found to have no circadian rhythm in calves (11).…”
Section: Rumen Maturation At Early Agesupporting
confidence: 85%
“…Also, it could be attributed to the modification of the structure by adding CMSC (Desouky, in press). Previous results in Table 3 confirmed that the preparation of the formulas in Nano form improved texture profile (Dennis et al, 2018;Elemike et al, 2019). No marked change occurred in color and appearance (as shown in Figure 2) either in Nano wet or/and dried treatments.…”
Section: Texture Profile Of Different Nano Weaning Wet Formulassupporting
confidence: 73%
“…Thus, it would be advisable to conduct further research on both factors and their influence on the growth and development of calves. Voluntary MR and solid feed intake are different in individual calves [26,45], and should therefore be considered in further research about optimal weaning age. From this study, a later weaning regimen can be considered as advantageous in early life with potential consequences for later health and metabolic performance.…”
Section: Implications and Perspectivesmentioning
confidence: 99%